Adenocarcinomas of the esophagogastric junction are more likely to respond to preoperative chemotherapy than distal gastric cancer - Reim, Daniel; Ebert, Matthias (Annals of surgical oncology, 2012)
BackgroundPreoperative chemotherapy has been shown to improve outcome of patients with adenocarcinoma of the esophagogastric junction (AEG) and gastric cancer (GC), and histopathologic response has been identified as an independent prognostic parameter in these patients. A recent meta-analysis has identified patients with AEG as benefiting more from preoperative chemotherapy than patients with GC. The aim of this retrospective analysis was to prove these findings in an experienced single-center large patient cohort because there are currently no recruiting prospective clinical trials.MethodsIn a single center, 551 patients underwent preoperative platin-based chemotherapy followed by oncologic surgery for locally advanced AEG and GC. Pretherapeutic clinical parameters were correlated with histopathologic response to preoperative chemotherapy.ResultsHistopathologic response (<10% of residual tumor) was found in 130 patients (24%) and was significantly correlated with overall survival (P < 0.0001). Tumor localization at the esophagogastric junction (GE junction), lower baseline cT stage, and baseline cN0 stage were significantly associated with histopathologic response (P = 0.034, P = 0.015, and P = 0.002, respectively). In subgroup analyses, the latter two predictive parameters were confirmed only for AEG (n = 378) but not for other GC (n = 173). AEG patients who were pretherapeutically staged as having cT3/4, cN0 disease (n = 73) were identified as the subgroup with the highest rate of histopathologic response (48%).ConclusionsAEG is more likely to respond to preoperative chemotherapy than GC, a finding that might help identify patients who would benefit from preoperative chemotherapy.